Fostering Personal Growth Through Self-Regulation: The Roles of Cognitive, Affective, and Motivational Feedback - Andi Dio Nurul Awalia; Sanatang Sanatang; M. Miftach Fakhri; Kurnia Prima Putra; Pramudya Asoka Syukur; Soeharto Soeharto (Online Learning In Educational Research (OLER), 2026)
Feedback plays a fundamental role in supporting students’ learning and personal development, yet previous studies have largely examined cognitive and affective feedback separately, providing limited understanding of how they jointly promote personal growth through self-regulation. This study investigated the relationships among cognitive feedback, affective feedback, motivation, self-regulation, and personal growth and understanding in higher education. A quantitative cross-sectional design was employed involving 450 university students, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings demonstrate that cognitive feedback, affective feedback, and learning motivation each make meaningful contributions to strengthening students’ self-regulation. In turn, self-regulation emerged as a key predictor of personal growth and deeper understanding while also serving as the mechanism through which feedback and motivation influence these outcomes. These findings underscore the importance of integrating cognitive and affective feedback practices to cultivate students’ motivation, strengthen self-regulated learning, and support holistic personal development. The study contributes an integrated feedback framework that highlights self-regulation as a central process linking instructional feedback to meaningful learning and personal growth in higher education